0
$\begingroup$

Find the equation of the tangent line to the polar curve: $r=3-3\sin\theta$ at $\theta=\frac{3\pi}{4}$

I have the equation: $$\frac{dy}{dx} =\frac{\frac{dy}{d\theta}}{\frac{dx}{d\theta}}=\frac{\frac{dr}{d\theta}\sin\theta+r\cos\theta}{\frac{dr}{d\theta}\cos\theta-r\sin\theta}= \frac{-3\cos\theta\sin\theta+(3-3\sin\theta)\cos\theta}{-\cos^2\theta-(3-3\sin\theta)\sin\theta}=2\sqrt{2}-3$$

which, if I did the math correctly (if I didn't could someone point it out), is the slope of the tangent line. How do I find the equation?

$\endgroup$
  • $\begingroup$ Where "do you have" that equation from? $\endgroup$ – Timbuc Oct 27 '14 at 3:35
  • $\begingroup$ because $x=r\cos\theta$, $y=r\sin\theta$ $\endgroup$ – Jessica Oct 27 '14 at 4:30
  • $\begingroup$ Sorry, I still don't understand. $\endgroup$ – Timbuc Oct 27 '14 at 4:35
1
$\begingroup$

This seems to be the question that I answered earlier. $x_0 = r\cos \theta = (3 - 3\sin 3\pi/4)\cos 3\pi/4$, and similarly you can find $y_0$, and then use $y - y_0 = m(x - x_0)$ with $m = 2\sqrt{2}-3$

$\endgroup$
  • $\begingroup$ Just looked at your answered question, and it is the same. Although, I did get a different slope. $\endgroup$ – Jessica Oct 27 '14 at 3:42
  • $\begingroup$ so it would just be $y-3\sin\theta-3\sin^2\theta = (2\sqrt{2}-3)(x-3\cos\theta-3\sin\theta\cos\theta)$? $\endgroup$ – Jessica Oct 27 '14 at 4:36
  • $\begingroup$ I got $y = (1-\sqrt{2})x+2\frac{3\sqrt{2}-3}{2}$ $\endgroup$ – Jessica Oct 27 '14 at 5:41
  • $\begingroup$ oh yeah, I edited it above. Is that correct? $\endgroup$ – Jessica Oct 27 '14 at 5:47
  • $\begingroup$ Cancel the two $2$. $\endgroup$ – DeepSea Oct 27 '14 at 5:51
1
$\begingroup$

Ok, the formula is correct (look at the comments), so that indeed

$$\frac{dy}{dx}=\frac{\frac{dr}{d\theta}\sin\theta+r\cos\theta}{\frac{dr}{d\theta}\cos\theta-r\sin\theta}$$

But at $\;\theta=\frac{3\pi}4\;$ :

$$\frac{dr}{d\theta}_{\theta=\frac{3\pi}4}=-3\cos\theta_{\theta=\frac{3\pi}4}=\frac3{\sqrt2}$$

$$r\cos\theta=(3-3\sin\theta)\cos\theta\stackrel{\theta=\frac{3\pi}4}\longrightarrow\;\;=\left(3-\frac3{\sqrt2}\right)\left(-\frac1{\sqrt2}\right)=\frac32-\frac3{\sqrt2}$$

$$r\sin\theta=(3-3\sin\theta)\sin\theta\stackrel{\theta=\frac{3\pi}4}\longrightarrow\;\;=\left(3-\frac3{\sqrt2}\right)\left(\frac1{\sqrt2}\right)=\frac3{\sqrt2}-\frac32$$

So

$$\frac{dy}{dx}|_{\theta=\frac{3\pi}4}=\frac{\frac3{\sqrt2}\frac1{\sqrt2}+\frac32-\frac3{\sqrt2}}{\frac3{\sqrt2}\left(-\frac1{\sqrt2}\right)-\frac3{\sqrt2}+\frac32}=\frac{3-\frac3{\sqrt2}}{-\frac3{\sqrt2}}=-\frac{1-\frac1{\sqrt2}}{\frac1{\sqrt2}}=1-\sqrt2$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.